Neural pathways underlying the interplay between emotional experience and behavior, from old theories to modern insight - Stanojlović, Olivera; Šutulović, Nikola; Hrnčić, Dragan; Mladenović, Dušan; Rašić-Marković, Aleksandra; Radunović, Nebojša; Vesković, Milena (Archives of Biological Sciences, 2021)
Paper description: The historical development of the perception of emotions from the beginning of emotion elucidation to contemporary theories of doctors, neuropsychologists, neuroscientists, neurologists and psychiatrists are examined. Modern theories are surveyed by a bottom-up approach, a stimulus-focused view of emotional processing that considers the stimulation of the amygdala which recognizes affectively visible stimuli, creating behavioral and visceral responses, and a top-down approach, a cognition-focused view of emotional processing that considers activation of the system for selective attention, working memory, speech, enabling conscious decisions to be made in different situations. Abstract: Emotions are specific psychological states brought about by neurophysiological changes associated with feelings, thoughts and behavioral responses. Emotions were considered as irrational experiences beyond the domain of logical perception because of their intertwinement with mood, temperament, creativity, motivation and personality. Through the centuries, emotions have been the focus of research among great classical philosophers, doctors, neuropsychologists, neuroscientists, neurologists and psychiatrists. The neurophysiological basis of behavior, such as emotional facial expression, and autonomic events in the physiological theory of William James and James-Lange and modified by Cannon-Bard, was followed by the two-factor theory of emotions of Schachter-Singer and Lazarus’ higher-order cognitive evaluation. Four components that influence each other represent the concept of emotions and complete the overall emotional experience, and these are: autonomous (increase in heart rate, blood pressure); somatic (body language, facial expressions); cognitive (control, management), and subjective feeling (emotion, individual experience). The interplay between emotions and cognition has been the subject of research. Emotions can be evoked reflexively by simple physical stimuli (bottom-up), but can also be complex reactions involving cognitive, physiological and behavioral reactions (top-down). The amygdala, the “alert" or “neural alarm” structure, is responsible for conditioning fear, while the medial prefrontal cortex participates in emotion self-regulation and decision making.